THE IMPORTANCE OF NEUROPHYSIOLOGICAL DATA IN PSYCHOLOGY - Ro'ziyeva Laylo Ravshan qizi; Oymatova Dilorom Ro'zimurotovna (Western European Studies, 2025)
This thesis highlights the role and importance of neurophysiological data in psychology. The biological basis of mental processes in the brain, the functioning of the nervous system and its impact on human mental states are analyzed. The functional significance of brain regions, neurophysiological mechanisms of mental disorders, diagnostic and therapeutic approaches are considered in detail. The application of neurophysiological approaches in educational and developmental psychology, their role in developing individual approaches and pedagogical strategies are also revealed. The conclusion substantiates the relevance of interdisciplinary integration and the need for a modern psychologist to have neurobiological knowledge. The work has scientific, theoretical and practical significance and can be an important methodological resource in psychology education.
Keywords: important; Psychology; neurophysiology; mozgovaya deyatelnost